Pope Francis : conversations with Jorge Bergoglio - Francis, Pope, 1936-; Francis, Pope, 1936-; Rubn̕, Sergio; Ambrogetti, Francesca (New York : G. P. Putnam's Sons, 2013)
"This book, first published in 2010, is the fruit of a series of journalistic interviews with Bergoglio when he was cardinal, consecrated by Pope John Paul II. They give insight into his core beliefs, his personal history, his widsom, intellect, compassion, humility, and ultimately his humanity. Here--in his own words--is an intimate look at the man who is now the leader of the Roman Catholic Church"--Page ix
"Originally published as El Jesuita: Conversaciones con Jorge Bergoglio, c2010 Sergio Rubin and Francesca Ambrogetti."
Keywords: Francis, -- Pope, -- 1936- -- Interviews; Jesuits -- Argentina -- Interviews; Cardinals -- Argentina -- Interviews